Inter-Population Similarities and Differences in Predation Efficiency of a Mosquito Natural Enemy. Issue 6 (27th May 2020) - Cuthbert, Ross N; Dalu, Tatenda; Wasserman, Ryan J; Weyl, Olaf L F; Froneman, P William; Callaghan, Amanda; Dick, Jaimie T A
Abstract: Predation is a critical factor that mediates population stability, community structure, and ecosystem function. Predatory natural enemies can contribute to the regulation of disease vector groups such as mosquitoes, particularly where they naturally co-occur across landscapes. However, we must understand inter-population variation in predatory efficiency if we are to enhance vector control. The present study thus employs a functional response (FR; resource use under different densities) approach to quantify and compare predatory interaction strengths among six populations of a predatory temporary pond specialist copepod, Lovenula raynerae, from the Eastern Cape of South Africa preying on second instar Culex pipiens complex mosquito larvae. All individuals from the sampled populations were predatory and drove significant mortality through per capita predation rates of 0.75–1.10 mosquitoes/h at maximum densities over a 5-h feeding time. Individuals from all copepod populations exhibited Type II FRs with no significant differences in attack rates. On the other hand, there were significant differences in handling times, and therefore also maximum feeding rates (maximum experimental prey density: 32), suggesting possible genetic differences among populations that influenced predation. Owing to a widespread distribution in arid landscapes, we propose that predatory calanoid copepods such as L. raynerae play a key regulatory role at the landscape scale in the control of disease vector mosquito populations. We propose that these ecosystems and their specialist biota should thus be conserved and enhanced (e.g., via selective breeding) owing to the ecosystem services they provide in the context of public health.